In memoriam - CPH 51(1-2) (Czasopismo Prawno-Historyczne, 1999)
Barbara Waldo, 1925-1998 (Zygfryd Rymaszewski) ... 499 Jan Malarczyk, 1931-1998 (Lech Dubel) ... 501 Franciszka Ryszka, 1924-1998 (Henryk Olszewski) ... 505